Clinical Decision Support Stewardship: Best Practices and Techniques to Monitor and Improve Interruptive Alerts - Chaparro, Juan D.; Beus, Jonathan M.; Dziorny, Adam C.; Hagedorn, Philip A.; Hernandez, Sean; Kandaswamy, Swaminathan; Kirkendall, Eric S.; McCoy, Allison B.; Muthu, Naveen; Orenstein, Evan W. (Applied Clinical Informatics, 2022)
Interruptive clinical decision support systems, both within and outside of electronic health records, are a resource that should be used sparingly and monitored closely. Excessive use of interruptive alerting can quickly lead to alert fatigue and decreased effectiveness and ignoring of alerts. In this review, we discuss the evidence for effective alert stewardship as well as practices and methods we have found useful to assess interruptive alert burden, reduce excessive firings, optimize alert effectiveness, and establish quality governance at our institutions. We also discuss the importance of a holistic view of the alerting ecosystem beyond the electronic health record.
Keywords: linical information system use, administration, and maintenance; clinical decision support; organizational change management mixed methodologies; socio-technical aspects of information technology